Virtual reality videos used in undergraduate palliative and oncology medical teaching: results of a pilot study. (26th February 2019) - Taubert, Mark; Webber, Lucie; Hamilton, Timothy; Carr, Madeleine; Harvey, Mark
Abstract : Background: Virtual reality (VR) immersive environments have been shown to be effective in medical teaching. Our university hospital received funding from our deanery, Health Education in Wales, to film teaching videos with a 360-degree camera. Aims: To evaluate whether VR is an effective and acceptable teaching environment. VR headsets were set up for medical students who rotated through Velindre Cancer Hospital's Palliative Care department. Methods: Students were asked to put on a VR headset and experience a pre-recorded 27 min presentation on nausea and vomiting in palliative care settings. They subsequently viewed a radiotherapy treatment experience from a patient's point of view. Results: Of the 72 medical students who participated, 70 found the experience comfortable, with two students stating they felt the experience uncomfortable (1=headset too tight; 1=blurry visuals). Numerical scoring on ability to concentrate in VR from 0 to 10 (0=worst, 10=best) scored an average of 8.44 (range, 7–10). Asked whether this format suited their learning style, average score was 8.31 (range 6–10). 97.2 % (n=70) students stated that they would recommend this form of learning to a colleague, with one student saying he/she would not recommend and another stating he/she was unsure. Students left anonymous free-text feedback comments which helped frame future needs in this emerging area. Discussion: This study suggests that there is room for exploring new ways of delivering teaching and expanding it more widely in palliative care and oncology, but also provides feedback on areas that need further careful attention. Comments from students included: "Might have been the novelty factor but I learnt more from this 20 min VR thing than I have from many lectures". Summary: The project has proved sufficiently popular in medical student feedback, that the VR experience is now available on YouTube and has been permanently introduced into routine teaching. Further 360-degree teaching environments have been filmed. Of note is that our 360-degree videos have been viewed in Africa, so this format of teaching could prove valuable due to its global reach.